(untitled) (Research, Society and Development, 2022)
Species of the genus Croton L., especially Croton lechleri Müll. Arg. popularly known as "dragon blood", are used for various therapeutic purposes by the Brazilian population. In vitro assays evaluating the cytotoxicity of this plant in healthy cells are scarce. Thus, this study aims to evaluate the cellular toxicity of the ethanolic extract of C. lechleri bark, and compare it with commercially available compounds such as quinoleic compounds and avermectins. The hemolytic test was performed by adding the extract in red cells suspension in saline at a hematocrit of 10% with decreasing concentrations. The cytotoxicity assay was performed on VERO cells maintained in RPMI culture medium supplemented with fetal bovine serum, to which 7 concentrations diluted 1/2 from the stock solution of 500 µg/mL of the crude extract of C. lechleri and the drugs Chloroquine, Hydroxychloroquine and Ivermectin. Hemolysis was analyzed using a UV/VIS at intervals of 30, 60 and 120 minutes. Cytotoxicity after 72 hours by resazurin reduction assay. The results showed that the extract of C. lechleri at different concentrations and times, showed low or no toxicity to red blood cells. In the cytotoxicity assay, the extract presented CC₅₀ of 218,9 µg/mL, the CQ, HCQ and IVe of 128,5; 191,6 and 32,9 µg/mL, respectively. It was concluded that the ethanolic extract of C. lechleri bark did not present significant hemolysis and that it presented moderate cytotoxicity against VERO cells, showing that this natural product is potentially safe for popular use.